A marker-and-cell approach to free surface 2-D multiphase flows - Santos, F. L. P. [UNESP]; Ferreira, V. G.; Tome, M. F.; Castelo, A.; Mangiavacchi, N.; McKee, S. (Wiley-Blackwell, 2012)
This work describes a methodology to simulate free surface incompressible multiphase flows. This novel methodology allows the simulation of multiphase flows with an arbitrary number of phases, each of them having different densities and viscosities. Surface and interfacial tension effects are also included. The numerical technique is based on the GENSMAC front-tracking method. The velocity field is computed using a finite-difference discretization of a modification of the NavierStokes equations. These equations together with the continuity equation are solved for the two-dimensional multiphase flows, with different densities and viscosities in the different phases. The governing equations are solved on a regular Eulerian grid, and a Lagrangian mesh is employed to track free surfaces and interfaces. The method is validated by comparing numerical with analytic results for a number of simple problems; it was also employed to simulate complex problems for which no analytic solutions are available. The method presented in this paper has been shown to be robust and computationally efficient. Copyright (c) 2012 John Wiley & Sons, Ltd.
Keywords: marker-and-cell; multiphase flows; surface tension; free surface flows; numerical simulation; finite difference